Training and Diffusion of Change: The Impact of Training and Proactivity on Change-Related Advice Giving. (December 2019) - Kim, Byeong Jo; Rousseau, Denise M.; Tomprou, Maria
This study investigates the effects of organizational change–related training on the diffusion of change through the employee advice network. It also examines the contribution of employee proactivity to the effects of that training. We compare trainees ( N = 46) and nontrained peers ( N = 47) doing similar work at pre- and posttest to examine how training and individual proactivity contribute to the change process. Results indicate that training is associated with increased change-related knowledge and skills and greater change-related advice giving (i.e., in-degree centrality). Additionally, proactivity is positively related to change-related advice giving and seeking (i.e., in- and out-degree centrality). Our findings also show that the effect of training on change-related advice giving is stronger for more proactive trainees than less proactive ones. We discuss our study's theoretical and practical implications for both organizational change and employee proactivity.